Fail, flip, fix, and feed – Rethinking flipped learning: A review of meta-analyses and a subsequent meta-analysis - Kapur, Manu; Hattie, John; Grossman, Irina; Sinha, Tanmay (Frontiers in Education, 2022)
The current levels of enthusiasm for flipped learning are not commensurate with and far exceed the vast variability of scientific evidence in its favor. We examine 48 meta-analyses only to find remarkably different overall effects, begging the question as to possible moderators and confounds, showing the need to control for the nature of the intervention. We then conducted a meta-analysis of 173 studies specifically coding the nature of the flipped implementation. Contrary to many claims, most in-class sessions are not modified based on the flipped implementation. Further, it was flipping followed by a more traditional class and not active learning that was more effective. Drawing on related research, we propose a more specific model for flipping, "Fail, Flip, Fix, and Feed" whereby students are asked to first engage in generating solutions to novel problems even if they fail to generate the correct solutions, before receiving instruction.